Социальные сети: история и анализ - Макатов, Е.К.; Актаева, А.О.; Кусаинова, У.Б.; Аусилова, Н.М. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
Социальные сети: история и анализ